Multivariate analysis in Indian mustard genotypes for morphological and quality traits - Rao Pankaj; Ram Avtar; Nisha Kumari; Minakshi Jattan; Babita Rani; Manmohan and; R.K. Sheoran (Electronic Journal of Plant Breeding, 2017)
Multivariate analysis was carried out with 20 morphological (including quantitative as well as qualitative) and five oil quality traits in 43 genotypes of Indian mustard. Principal factor analysis led to the identification of nine principal components (PCs) which explained about 77% variability. The first principal component (PC1) explained 16.65% of the total variation. The remaining PC’s explained progressively lesser and lesser of the total variation. Varimax Rotation enabled loading of similar type of variables on a common principal factor (PF) permitting to designate them as seed yield and component traits, leaf, oil and its quality factors. Based on PF scores, the genotypes viz., RH(OE)0801, EC597320, EC597341, EC597344, EC592579, EC592584 and JM6014(YS) have been identified superior for seed yield/plant, while the genotypes JM6009, JM6011, EC697334 and ZEM-1were found superior for oil content. Similarly, the genotypes JM6009, NUDBYJ-10, Pusa Mustard-21, RLC-2 and ZEM-2 showed superiority for erucic acid, whereas genotypes JM6004(YS), JM6026 and EC552583 exhibited superiority for glucosinolate content. These genotypes may further be utilized in breeding programmes for evolving mustard varieties having high seed yield and oil content; and with superior oil quality. Hierarchical cluster analysis resulted into eight clusters containing one to 16 genotypes. The results of cluster and principal factor analyses confirmed each other.